The Use of Contrast-Enhanced Ultrasound (CEUS) in the Evaluation of the Neonatal Brain - Domen Plut; Maja Prutki; Peter Slak (Children, 2023)
In recent years, advancements in technology have allowed the use of contrast-enhanced ultrasounds (CEUS) with high-frequency transducers, which in turn, led to new possibilities in diagnosing a variety of diseases and conditions in the field of radiology, including neonatal brain imaging. CEUSs overcome some of the limitations of conventional ultrasounds (US) and Doppler USs. It allows the visualization of dynamic perfusion even in the smallest vessels in the whole brain and allows the quantitative analysis of perfusion parameters. An increasing number of articles are published on the topic of the use of CEUSs on children each year. In the area of brain imaging, the CEUS has already proven to be useful in cases with clinical indications, such as hypoxic-ischemic injuries, stroke, intracranial hemorrhages, vascular anomalies, brain tumors, and infections. We present and discuss the basic principles of the CEUS and its safety considerations, the examination protocol for imaging the neonatal brain, and current and emerging clinical applications.